2011
DOI: 10.1097/iop.0b013e3181cff671
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Two Scleral Flaps Evisceration Technique: Analysis of 201 Procedures

Abstract: The 2 scleral flaps evisceration technique is a simple, safe, and useful procedure that enables filling the orbital socket with an adequate orbital implant size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
0
16
0
3
Order By: Relevance
“…2,3,6,7,9,[13][14][15][16][17][18][19][20][21] The wide range of complication rates reported is likely due to variability in patient demographics, underlying ocular pathology, surgical technique (including type and size of implant, wrapping material, and presence or absence of sclerotomies), and duration of follow-up (with longer follow-up being associated with a higher incidence of complications). 6,9,13,14,16,21 Collectively, recent reports have an average incidence of 8.6% for implant exposure, 1.0% for surgical site infection, and 2.5% for superior sulcus deformity. 2,3,6,7,9,[13][14][15][16][17][18][19][20][21] Our study found that primary resident cases had a below-average incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6,7,9,[13][14][15][16][17][18][19][20][21] The wide range of complication rates reported is likely due to variability in patient demographics, underlying ocular pathology, surgical technique (including type and size of implant, wrapping material, and presence or absence of sclerotomies), and duration of follow-up (with longer follow-up being associated with a higher incidence of complications). 6,9,13,14,16,21 Collectively, recent reports have an average incidence of 8.6% for implant exposure, 1.0% for surgical site infection, and 2.5% for superior sulcus deformity. 2,3,6,7,9,[13][14][15][16][17][18][19][20][21] Our study found that primary resident cases had a below-average incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Typical complications of evisceration include infection and wound dehiscence with implant exposure or extrusion, as well as minor surgical sequelae such as eyelid malposition, superior sulcus deformity, enophthalmos, and cyst formation. 7,[13][14][15][16][17][18][19][20][21] Current literature explores various surgical techniques, efforts to minimize complications, and long-term outcomes of anophthalmic sockets. Many of these published works arise from training institutions.…”
mentioning
confidence: 99%
“…Also in 2007, Masdottir and Sahlin reported their experience using a split-sclera technique similar to Massry's and Hold's, where 5% developed exposure or extrusion of implant, but 78% of the patients felt pleased or very pleased with the operation 77. Most recently in 2011, Smith et al 78. reported their experience with Massry's and Hold's technique.…”
Section: Sclerotomymentioning
confidence: 99%
“…It is effective in volume replacement and implant exposure. 1,10,16,17 But there are some limitations of two-scleral flaps evisceration method. Forward displacement of both flaps for overlapping distends horizontal and vertical muscles so antagonist muscles counteract against the other.…”
Section: -13mentioning
confidence: 99%